Comparison of the effects of sugammadex and neostigmine on postoperative nausea and vomiting - Yağan,Özgür (2017)
Abstract Background and objectives: The aim of our study is to compare the effects of sugammadex and neostigmine, used for neuromuscular blockage antagonism, on postoperative nausea and vomiting (PONV). Methods: Our study was completed with 98 ASA I-II risk patients undergoing endotracheal intubation under general anesthesia. At the end of the surgery patients were randomly divided into two groups given 2 mg kg-1 sugammadex (Group S) or 50 µg kg-1 neostigmine plus 0.2 mg kg-1 atropine (Group N). Monitoring and recording times were set as 1 hour postoperative and from 1-6, 6-12, and 12-24 hours. The anti-emetic amounts administered were recorded. Results: In the first hour postoperative 13 patients in Group N (27%) and 4 in Group S (8%) were observed to have nausea and/or vomiting and the difference was statistically significant (p = 0.0016). During the 24 hours of monitoring there was no significant difference in the incidence and severity of PONV (p > 0.05), however the number of patients given ondansetron for PONV treatment in Group N was statistically significantly higher than the number in Group S (16 in Group N, 6 in Group S, p < 0.011). Conclusions: At the end of our study comparing neostigmine with sugammadex for neuromuscular blockage antagonism, we found use of sugammadex had lower incidence of PONV in the postoperative 1st hour and less anti-emetic use in 24 hours of monitoring.